1996
DOI: 10.1046/j.1525-1438.1996.06030225.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of beta carotene vs placebo for the treatment of cervical HPV infection

Abstract: The objective of the study was to determine if oral beta carotene would improve abnormalities observed in Papanicolaou smears or reduce the amount of HPV DNA in genital samples. A randomized double blind placebo controlled trial was designed for 117 women with abnormal cervical morphology, not undergoing laser ablative therapy, at The Royal Women’s Hospital, Victoria. Thirty milligrams of oral beta carotene were administered daily for 12 months. Post‐intervention cervical cytology and the amount of HPV DNA pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Using a 10 mg day −1 dose in a randomized trial with a 3-month follow up, de Vet et al (1991) found a small, non-significant difference in regression that changed direction depending on whether the broad or strict definitions of regression were used (see Table 3). Using a longer follow-up in women with less severe lesions, neither Fairley et al (1996) nor Romney et al (1997) found a difference in regression rates over 9-12 months with a daily dose of 30 mg. Fairley et al (1996) found no difference in the quantity of DNA from human papilloma virus between the groups and Romney et al (1997) found a non-significant adverse effect of beta-carotene on persistence of HPV. Based on the four randomized trials, the results of Manetta et al (1996), who found a 70% regression of CIN I and II over 6 months in an uncontrolled trial of beta-carotene, must be regarded as being due to spontaneous regression rather than a positive effect of beta-carotene.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Using a 10 mg day −1 dose in a randomized trial with a 3-month follow up, de Vet et al (1991) found a small, non-significant difference in regression that changed direction depending on whether the broad or strict definitions of regression were used (see Table 3). Using a longer follow-up in women with less severe lesions, neither Fairley et al (1996) nor Romney et al (1997) found a difference in regression rates over 9-12 months with a daily dose of 30 mg. Fairley et al (1996) found no difference in the quantity of DNA from human papilloma virus between the groups and Romney et al (1997) found a non-significant adverse effect of beta-carotene on persistence of HPV. Based on the four randomized trials, the results of Manetta et al (1996), who found a 70% regression of CIN I and II over 6 months in an uncontrolled trial of beta-carotene, must be regarded as being due to spontaneous regression rather than a positive effect of beta-carotene.…”
Section: Discussionmentioning
confidence: 93%
“…Firstly, we excluded anyone who had a histological diagnosis of CIN II or III whereas about two-thirds of the Dutch subjects (de Vet et al, 1991) and half the American subject (Romney et al, 1997) had these more severe lesions. Our study subjects generally had more severe lesions than those of Fairley et al (1996) and we did not allow the presence of HPV alone as a sufficient entry criterion. In addition, our entry criteria were based on three forms of assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Four classes of agents have been used in chemoprevention trials in the cervix: retinoids, micronutrients, polyamine synthesis inhibitors, and adduct reducers (Table 2) (Current Clinical Trials Oncology, 1994aBell et al, 2000;Butterworth et al, 1992a;Butterworth et al, 1992b;Childers et al, 1995;de Vet et al, 1991;Fairley et al, 1996;Pollen et al, 2001a;Keefe 1998;Mackerras et al, 1999;Manetta et al, 1996;Meyskens et al, 1983;Meyskens et al, 1994;Mitchell et al, 1998;Romney et al, 1987;Romney et al, 1985;Romney et al, 1997;Ruffin et al, 1999;Surwit et al, 1982;Weiner et al, 1986) Retinoids have inhibitory effects on the growth of HPV; specifically, there are several mechanisms by which retinoic acid is thought to affect the HPV E6 and E7 transforming proteins. Bartsch et al (1992) have demonstrated that in the presence of retinoic acid there is decreased expression of HPV messenger RNA.…”
Section: Chemoprevention Agents and Hpv Expressionmentioning
confidence: 99%
“…In a β-carotene supplement study conducted in the Netherlands, 278 women with cervical intraepithelial neoplasia (CIN) were administered either 10 mg of β-carotene or placebo daily for a 3-month period, and no effect of β-carotene on regression was observed [9]. Fairley et al [10] assigned 111 women with cytologic abnormalities to receive 30 mg/d of β-carotene or placebo and found no beneficial effects. Romney et al [11] reported no effects of supplementation in a doubleblinded trial in which 30 mg of β-carotene or placebo was administered daily to 98 patients with CIN (primarily CIN I), who were followed for 9 months.…”
Section: Carotenoidsmentioning
confidence: 99%